2018
DOI: 10.1051/e3sconf/20183111014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding customers’ intention to use social network sites as complaint channel: an analysis of young customers’ perspectives

Abstract: Social network sites (SNSs) have grown rapidly in recent years. More and more companies have used SNSs as part of their business strategy. SNSs offer numerous advantages, especially in enhancing communication. SNSs have a potential as a new complaint channel for young customers to file their complaints to companies. The objective of this study is to investigate the acceptance of SNSs as complaint channel based on TAM. A structured questionnaire was distributed to young participants, which collected 222 valid q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
6
0
7
Order By: Relevance
“…Table 10 shows that all categories have insignificant relationship between PEOU and impact on business. Setiawan, Setyohadi, and Pranowo (2018) have found that PEOU is not significant with their research findings. It is possibly because there are other technologies that are easier to use.…”
Section: N P R E S Smentioning
confidence: 67%
“…Table 10 shows that all categories have insignificant relationship between PEOU and impact on business. Setiawan, Setyohadi, and Pranowo (2018) have found that PEOU is not significant with their research findings. It is possibly because there are other technologies that are easier to use.…”
Section: N P R E S Smentioning
confidence: 67%
“…Thus, it is possible that factors relating to perceived critical mass, perceived usefulness and information-and resource-sharing capability may not come across as genuinely advantageous to these digital natives. In support of this postulation are a myriad of studies that similarly reached conclusions stating that users' adoption of social-media platforms for collaborative learning was not likely to be attributable to perceived critical mass [68,69], perceived usefulness [70,71,72], or information-and resource-sharing capability [72,73,74].…”
Section: Discussionmentioning
confidence: 93%
“…Sehingga mengakibatkan krisis privasi dari para pengguna social media (sosmed). Media sosial merupakan salah satu aktivitas online favorit yang digunakan oleh publik hampir setiap hari [1]. Laporan yang pernah dikeluarkan oleh Global Web Index pada tahun 2015 lalu mengenai trend terbaru berkenaan dengan jejaring sosial menemukan bahwa setiap empat menit yang dihabiskan seseorang di internet digunakan untuk mengakses jejaring sosial, seiring dengan peningkatan penggunaan internet pada smartphone [2].…”
Section: Pendahuluanunclassified